Answer: M^-1 L^-3T^4A^2
Explanation:
From coloumb's law
K = q1q2 / (F × r^2)
Where;
q1, q2 = charges
k = constant (permittivity of free space)
r = distance
Charge (q) = current(A) × time(T) = TA
THEREFORE,
q1q2 = (TA) × (TA) = (TA)^2
Velocity = Distance(L) / time(T) = L/T
Acceleration = change in Velocity(L/T) / time (T)
Therefore, acceleration = LT^-2
Force(F) = Mass(M) × acceleration (LT^-2)
Force(F) = MLT^-2
Distance(r^2) = L^2
From ; K = q1q2 / (F × r^2)
K = (TA)^2 / (MLT^-2) (L^2)
K = T^2A^2M^-1L^-1T^2 L^-2
COLLEXTING LIKE TERMS
T^2+2 A^2 M^-1 L^-1-2
M^-1 L^-3T^4A^2